2018
DOI: 10.1021/acs.chemrestox.8b00264
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Glyoxal-Induced DNA Cross-Links and Hemoglobin Modifications in Human Blood Measured by Mass Spectrometry

Abstract: Glyoxal is an oxoaldehyde generated from the degradation of glucose-protein conjugates and from lipid peroxidation in foods and in vivo, and it is also present in the environment (e.g., cigarette smoke). The major endogenous source of glyoxal is glucose autoxidation, and the glyoxal concentrations in plasma are higher in diabetic patients than in nondiabetics. Glyoxal reacts with biomolecules forming covalently modified DNA and protein adducts. We previously developed sensitive and specific assays based on nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Furthermore, hemoglobin can be obtained in pure form for analysis, so that interference from other proteins is minimal. Most importantly, levels of hemoglobin adducts are strongly correlated with DNA adducts of the same reactive species, as demonstrated in the cases of glyoxal, styrene, and 4-aminobiphenyl. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, hemoglobin can be obtained in pure form for analysis, so that interference from other proteins is minimal. Most importantly, levels of hemoglobin adducts are strongly correlated with DNA adducts of the same reactive species, as demonstrated in the cases of glyoxal, styrene, and 4-aminobiphenyl. …”
Section: Resultsmentioning
confidence: 99%
“…The level of hemoglobin modification can provide a measure of exposure averaged in a 2-month period. , It has been demonstrated that the degree of DNA adduction in blood leukocytes is strongly correlated with that of hemoglobin modifications from the same blood sample. Therefore, measuring the extent of hemoglobin modification in peripheral blood can serve as a surrogate to monitor DNA damage for the assessment of cancer risk . Hemoglobin can be conveniently obtained from a dried blood spot (DBS) card, a widely used biomonitoring technique .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, measuring the extent of hemoglobin modification in peripheral blood can serve as a surrogate to monitor DNA damage for the assessment of cancer risk. 52 Hemoglobin can be conveniently obtained from a dried blood spot (DBS) card, a widely used biomonitoring technique. 53 We demonstrated that tyrosine nitration, methionine oxidation, and other types of hemoglobin modifications (from glyoxal and methylglyoxal) are stable in the DBS card stored at room temperature for a minimum of 2 weeks.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Hemoglobin adducts have been considered as surrogate biomarkers in biomonitoring the exposure of chemicals and carcinogens in vivo. It is mainly owing to the high abundance of hemoglobin in the blood and its easy accessibility. In addition, the predictable lifetime of human hemoglobin and the lack of repair for protein adducts allow it to monitor the exposure of an individual on an average of 2 months. ,, …”
mentioning
confidence: 99%
“…In this laboratory, we have identified various post-translational modifications (PTMs) of hemoglobin in human blood, including methionine and cysteine oxidation, glutathionylation of cysteine, chlorination, nitrosylation, and nitration of tyrosine, and carboxymethylation, carboxyethylation, and hydroimidazolone of lysine and arginine residues. , In addition, methylation and ethylation sites were identified on the N -termini, histidine, lysine, cysteine, and glutamate residues. , The extents of modification with specific types and sites were quantified relative to the native reference peptide (NRP) in the tryptic digest of hemoglobin. Among them, the extent of certain nitrotyrosine, glutathionylated cysteine, and ethylated residues are greater in smokers compared to nonsmokers, ,, while chlorotyrosine and glyoxal- and methylglyoxal-induced modification are elevated in diabetic patients. ,, …”
mentioning
confidence: 99%